Comparison of stereotactic body radiation therapy with hepatic resection and radiofrequency ablation as initial treatment in patients with early-stage hepatocellular carcinoma - Yang, Zi-liang; Sun, Xu-qi; Tang, Yu-hao; Xiong, Pei-yao; Xu, Li (Frontiers in Oncology, 2022)
Background: The outcomes of Stereotactic body radiation therapy (SBRT), liver resection (LR) and radiofrequency ablation (RFA) as the initial treatment for AJCC stage-I HCC patients remains unclear. Methods: Patients with AJCC stage-I HCC from the Surveillance, Epidemiology and End Results database were analyzed and stratified according to tumor size: S subgroup (≤2cm), M subgroup (>2-3 cm), and L subgroup (>3cm). Propensity score matching was performed. Results: 4002 patients were included, the difference of median overall survival (mOS) between the SBRT group and the LR or RFA group in S subgroup was statistically insignificant (P=0.109 and P=0.744), but the mOS of the RFA group was significantly worse than the LR group (P <0.001). In M and L subgroup, the mOS of the SBRT group was worse than the RFA group (P=0.040 and P<0.001). The mOS of LR was the best comparing with either SBRT or RFA group regardless of the subgroup M or L (all P<0.001). Conclusion: For HCC ≤ 2 cm, SBRT can be used as an alternative treatment for RFA, RFA can provide better long-term survival than SBRT in patients with HCC lager than 2 cm, while LR remains the best choice.